Introduction to Copyright and Collective Management in Competition Law - Sladič, Jorg (LeXonomica, 2021)
Copyright is an absolute intellectual property right. Historically it is of territorial nature. One of the central issues of copyright is the remuneration of authors. Copyright confers to its holder a legal monopoly comprising certain economic rights that are granted for pecuniary consideration. The economically most efficient way of management of copyright's pecuniary consideration is collective management. However, collective management covers due to the territorial nature of copyright only territory of a certain state. In competition law that might be considered as a monopoly by collecting societies limited to borders of states, in other words, there are issues of possible abuse of a dominant position.Avtorska pravica je absolutna pravica intelektualne lastnine. Zgodovinsko je teritorialne narave. Eno od bistvenih vprašanj avtorske pravice je plačilo avtorjev. Avtorska pravica imetnikom podeli zakonit monopol nad nekaterimi materialnimi avtorskimi pravicami, ki se odstopijo odplačno. Ekonomsko najbolj učinkovitejši način upravljanja denarnega plačila za avtorske pravice je kolektivno upravljanje. Zaradi teritorialne narave avtorske pravice to zajema zgolj ozemlje določene države. To pa se v konkurenčnem pravu lahko obravnava kot monopolni oz. prevladujoč položaj organizacij za kolektivno upravljanje, s tem pa tudi vprašanje možne zlorabe takšnega položaja.